2020
DOI: 10.1038/s41586-019-1903-y
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification does not impair the behaviour of coral reef fishes

Abstract: The partial pressure of CO2 in the oceans has increased rapidly over the past century, driving ocean acidification (OA) and sparking concern for the stability of marine ecosystems 1-3 .Coral reef fishes are predicted to be especially susceptible to end-of-century OA, based on several high-profile papers reporting profound behavioural and sensory impairments (e.g., complete attraction to the chemical cues of predators under OA) 4,5 . In contrast, here we comprehensively and transparently show that end-of-centur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 55 publications
5
96
1
Order By: Relevance
“…In recent years, there has been a burgeoning of studies assessing the effects of future climate change scenarios on the fitness, physiology, and provision of ecosystem services in a plethora of marine species at both the macroscale, and increasingly, microscale. Many earlier studies have shown detrimental impacts of OA and warming scenarios on species performance, but increasingly, others do not (see Clark et al, 2020). Here, our results indicate that future predictions of sea surface temperature are likely to have detrimental effects on the ultrastructure of Mytilus sp., but when combined with atmospheric pCO 2 concentrations predicted for 2100, those negative effects will be in part, ameliorated.…”
Section: Discussionsupporting
confidence: 44%
“…In recent years, there has been a burgeoning of studies assessing the effects of future climate change scenarios on the fitness, physiology, and provision of ecosystem services in a plethora of marine species at both the macroscale, and increasingly, microscale. Many earlier studies have shown detrimental impacts of OA and warming scenarios on species performance, but increasingly, others do not (see Clark et al, 2020). Here, our results indicate that future predictions of sea surface temperature are likely to have detrimental effects on the ultrastructure of Mytilus sp., but when combined with atmospheric pCO 2 concentrations predicted for 2100, those negative effects will be in part, ameliorated.…”
Section: Discussionsupporting
confidence: 44%
“…While marine secondary producers such as zooplankton and tertiary producers such as fish can be indirectly affected by OA, through trophic transfer or food-web interactions, additional direct effects of OA often cannot be ruled out. As summarized in the comprehensive review by Nagelkerken and Munday (2016), behaviors of secondary and tertiary producers such as olfaction, phototaxis, lateralization, shelter, and escape can be altered by OA through multiple, non-exclusive mechanisms (also see recent studies by Schunter et al, 2016Schunter et al, , 2018Spady et al, 2018;Jarrold and Munday, 2019;Clark et al, 2020). This in turn will affect species interactions, population dynamics, community structure, and ultimately, biodiversity (Nagelkerken and Munday, 2016).…”
Section: Consequences Of Altered Community Composition Of Primary Promentioning
confidence: 99%
“…On the one-hand potential negative impacts have been found for the organ structure of larvae fish [15,17], hatching success [60], sensory abilities and behavior [61][62] or with respect to the survival in very early larval stages [13,63]. Early life stages prior to gill formation have a limited capacity for pH regulation [64] and are…”
Section: Conclusion and Discussionmentioning
confidence: 99%